Grooves surrounding the micropyle decrease the inseminating dose in fish - Pereira-Santos, Matheus [UNESP]; Shimoda, Eduardo; Cesar de Andrade, Andre Furugen; Silva, Luciano Andrade; Fujimoto, Takafumi; Senhorini, Jose Augusto; Yasui, George Shigueki; Okada Nakaghi, Laura Satiko [UNESP] (Cambridge Univ Press, 2017)
In fish with external fertilization, sperm must reach the oocyte through the micropyle to enter the cytoplasm. Fertilization success is then influenced by characteristics of oocytes or sperm. In this study, we evaluated oocyte morphology and sperm motility parameters and their effects on the inseminating dose in a teleost fish Astyanax altiparanae. Interestingly, we found one of the lowest yet described inseminating doses in teleosts (2390 spermatozoa oocyte(-1) ml(-1)). Such a fertilization efficacy may be explained by the long duration of sperm motility (>75 s), the small oocyte diameter (695.119 mu m), large micropyle diameter (7.57 mu m), and the presence of grooves on the oocyte surface that guides spermatozoon to the fertilization area. Additionally, we have described for the first time a structure that combines grooves on the chorion surface and a ridge in the micropylar area.
Keywords: Fertilization; Gametes; Morphology; Sperm; Teleosts